Challenges of teaching multilingual students in tertiary education - Huszti, Ilona; Lechner, Ilona (Educational Challenges, 2025)
Purpose. This study investigates the challenges faced by teachers of multilingual learners at the Ferenc Rákóczi II Transcarpathian Hungarian College of Higher Education in Ukraine. The college serves a diverse student population, including native Ukrainian speakers and Hungarian speakers, as well as speakers of other languages, creating a complex and dynamic multilingual learning environment. This research aims to understand the specific challenges faced by teachers in navigating this linguistic diversity to support all students' academic success. Methodology. A mixed-methods approach was employed for this research. Document analysis was conducted to examine the college's institutional language policies and their implications for teaching and learning. This included an analysis of official documents, such as the college charter and curriculum guidelines. Observational data was collected from multilingual classrooms simultaneously, to understand real-time language practices. Results. The findings reveal several key challenges. Firstly, addressing varying levels of proficiency in Ukrainian, Hungarian, and English within the same classroom presents significant pedagogical demands. Providing individualized support, including extra tutoring and language support services, was also identified as crucial for ensuring all students can engage effectively with the learning material. Secondly, the successful use of intermediary languages, such as English, in facilitating instruction across different language backgrounds proved to be a crucial consideration. Conclusions. The study underscores the complexities of teaching in a multilingual environment. It highlights the importance of teacher training and professional development in areas such as multilingual pedagogy, intercultural communication, and the development and utilization of appropriate language-learning resources. The findings of this study offer valuable insights for educators and policymakers in multilingual contexts, emphasizing the need for flexible and inclusive approaches to teaching and learning that address the unique linguistic and cultural needs of all students.